Thailand’s Automotive Service Quality Customer Satisfaction: A SERVQUAL Model CFA of Suzuki Motor - Chaichinarat, Pichaipat (Animo Repository, 2018)
Thailand’s automotive industry is the 12th largest in the world and plays an important role in Thailand’s economy. Under the government mandated Thailand 4.0 vision, the automotive sector has been identified as one of the 10 crucial sectors for future economic growth. Within this sector, service quality has repeatedly been identified as one of the most competitive factors amongst the major dealers. Service quality is a fundamental aspect of service provisioning, which demonstrates excellence and long-term success. The purpose of this paper is, therefore, to investigate service quality within Thailand’s Suzuki Motor Company by adopting the five dimensions of the SERVQUAL model (tangibles, reliability, responsiveness, assurance, empathy) for analysis. Additionally, the study also examined the validity of the service quality model and compared service quality satisfaction amongst Thailand’s Suzuki Motor Company service staff. By using multi- stage random sampling, 537 customers responded. Using both quantitative and qualitative research methods, the main research instrument was a questionnaire which used a 5-point Likert type agreement scale. An analysis was undertaken in which the mean ( standard deviation (S.D.), correlation analysis, and percentage were evaluated. Furthermore, a second-order confirmatory factor analysis was performed using Mplus Version 8 software. The statistical values were Chi-square = 2572.016, df = 979, RMSEA = .07, SRMR = .051, TLI =.901, CFI =.912. Results from the five identified dimensions were in line with the hypothesized model, with the weight of all the variables being positive. These included responsiveness, empathy, reliability, tangibility, and assurance.